2014
DOI: 10.1128/aac.01691-13
|View full text |Cite
|
Sign up to set email alerts
|

New Chemical Scaffolds for Human African Trypanosomiasis Lead Discovery from a Screen of Tyrosine Kinase Inhibitor Drugs

Abstract: Human African trypanosomiasis (HAT) is caused by the protozoan Trypanosoma brucei. New drugs are needed to treat HAT because of undesirable side effects and difficulties in the administration of the antiquated drugs that are currently used. In human proliferative diseases, protein tyrosine kinase (PTK) inhibitors (PTKIs) have been developed into drugs (e.g., lapatinib and erlotinib) by optimization of a 4-anilinoquinazoline scaffold. Two sets of facts raise a possibility that drugs targeted against human PTKs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 60 publications
(61 reference statements)
0
37
0
Order By: Relevance
“…We previously reported that the human tyrosine kinase inhibitor lapatinib ( 1 ), shown in Figure 1, prevents proliferation of bloodstream T. brucei with an EC 50 of 1.54 μM [17, 18]. Further optimization studies, especially the “tail” region (in red), led to the discovery of 2 (NEU-617), with a potency of 0.042 μM and improved parasite selectivity over 1 [12].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the human tyrosine kinase inhibitor lapatinib ( 1 ), shown in Figure 1, prevents proliferation of bloodstream T. brucei with an EC 50 of 1.54 μM [17, 18]. Further optimization studies, especially the “tail” region (in red), led to the discovery of 2 (NEU-617), with a potency of 0.042 μM and improved parasite selectivity over 1 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying pTyr-regulated pathways affected by lapatinib will help our understanding of the drug's antitrypanosomal activity in vitro or in a mouse model of HAT (5). Since pTyr serves as a docking site for effector proteins (12), we reasoned that polypeptides in complex with Tyr-phosphorylated proteins might provide some insight into processes regulated by that posttranslational modification.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical biology experiments confirmed that lapatinib treatment destabilizes the PFR structure and inhibits endocytosis of transferrin in bloodstream T. brucei. These two biological processes are essential for the parasite's viability, and their perturbation can explain, at least in part, lapatinib's ability to kill trypanosomes (4,5). This hypothesis-generating proteomics and chemical biology strategy could find general use in understanding the mode of action of other antiparasite hits discovered in phenotypic screens (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations